2014
DOI: 10.1007/s00167-014-2937-1
|View full text |Cite
|
Sign up to set email alerts
|

The variable morphology of suprascapular nerve and vessels at suprascapular notch: a proposal for classification and its potential clinical implications

Abstract: PurposeThe most common place for suprascapular nerve entrapment is the suprascapular notch. The aim of the study was to determine the morphological variation of the location of the suprascapular nerve, artery and vein, and measure the reduction in size of the suprascapular opening in each type of the passage. MethodsA total of 106 human formalin-fixed cadaveric shoulders were included in the study. After dissection of the suprascapular region, the topography of the suprascapular nerve, artery and vein was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 23 publications
4
44
1
Order By: Relevance
“…In aetiology of the SN entrapment, less attention has been paid to the topography of the complete suprascapular triad: the nerve, artery and vein [39]. The SSA which supplies the supraspinatus muscle enters the supraspinous fossa on the dorsal aspect of the scapula superior to the STSL [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In aetiology of the SN entrapment, less attention has been paid to the topography of the complete suprascapular triad: the nerve, artery and vein [39]. The SSA which supplies the supraspinatus muscle enters the supraspinous fossa on the dorsal aspect of the scapula superior to the STSL [26].…”
Section: Discussionmentioning
confidence: 99%
“…When the route of the SSA passes under the STSL, it may cause SN entrapment [6,44,49]. Polguj et al [39] found that specimens including type III suprascapular triad (the suprascapular vessels and nerve lie beneath the STSL) had smallest mean area of the suprascapular opening, when compared with the others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the locations of the associated suprascapular vein and artery are highly variable [16,20,22].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this is a very important subject, because the position of the suprascapular artery under the STSL could be one of the possible causes of SN entrapment [2,16,19,20].…”
Section: Introductionmentioning
confidence: 99%